Correlation between Dental Environment and Perceived Stress Scale among Dental Students during the COVID-19 Pandemic in Indonesia - Astoeti, Tri Erri; Josephine, Howis; Widyarman, Armelia Sari; Sudhana, Widijanto (UI Scholars Hub, 2021)
Academic stressors in a medical educational environment are related to two factors. This study was carried out in order to analyze the correlation between the dental environment and perceived stress among dental students during the COVID-19 pandemic. The respondents were 422 undergraduate dental students and the validated Modified Dental Environmental Stress (DES) and Perceived Stress Scale (PSS) questionnaires were used. Furthermore, the Spearman correlation analysis was used to measure the correlation between DES and PSS score. The result showed that five dental stressors were noted to have the strongest correlations with PSS (p-value >0.40). They include expectation towards dental school (p-value = 0.431), lack of confidence to be a successful dentist (p-value = 0.424), lack of confidence to become a successful dental student (p-value = 0.408), dental school regulations (p-value = 0.401) and criticism of school work (p-value = 0.400). In addition, all six DES categories showed a positive correlation with the PSS. Therefore, the dental students collectively displayed moderate perceived stress scores. The overall discoveries from this study showed a positive correlation between the DES and PSS among dental students during the COVID-19 pandemic.